Acute rupture of a liver hydatid cyst into the thorax - Castillo De la Cadena, Luis (2019)
Hydatid cyst is a human parasitic disease caused by the cystic stage of Echinococcus granulosus. There are hyperendemic areas of hydatidosis in Peru. Liver involvement is the common affection of the disease, rupture of liver cysts into the thorax is rare (less than 1% of cases). We present the case of a female patients who presented with a liver cyst rupture to the thorax, a multidisciplinary approach was needed to cure the patient.